Modified Cross‐Linking, Ligation, and Sequencing of Hybrids (qCLASH) to Identify MicroRNA Targets. Issue 10 (5th October 2021) - Gay, Lauren A.; Turner, Peter C.; Renne, Rolf
Abstract: This protocol was designed to identify microRNA (miRNA) targetomes from smaller‐input samples by performing a simplified workflow of the Cross‐Linking and Sequencing of Hybrids (CLASH) technique developed in the Tollervey group. In this ribonomics‐based technique, Cross‐Linking and Immunoprecipitation (CLIP) of Argonaute (Ago) is combined with an RNA ligase reaction that yields covalently bound "hybrids" between miRNAs and their target RNAs. While this iteration of CLIP identifies "high‐confidence" or "unambiguous" miRNA targets, the added ligation step is highly inefficient and therefore requires large numbers of cultured cells. To make this powerful approach applicable to smaller cell numbers, we created qCLASH, incorporating a workflow that performs all enzymatic reactions on bead‐bound complexes and omits gel purification of immunoprecipitated Ago complexes associated with major loss of RNA. At a sequencing depth of 100 million reads per library, which is highly feasible with rapidly decreasing sequencing costs, qCLASH, when used with three biological replicates, results in thousands of high‐confidence miRNA targets. qCLASH was first developed to identify viral miRNA targetomes of endothelial cells infected with Kaposi's sarcoma−associated herpesvirus. Since then, qCLASH has been applied to Epstein‐Barr virus− and MHV68‐infected cells, and more recently to metastatic melanoma and breast cancer cells. Currently, protocols are under development to apply qCLASH to human solid tumor specimens. © 2021 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol : Quick Cross‐Linking and Sequencing of Hybrids (qCLASH) Support Protocol : Optimization of Ago immunoprecipitation